Chemotherapy and diffuse low-grade gliomas: a survey within the European Low-Grade Glioma Network. Issue 4 (13th December 2018) - Darlix, Amélie; Mandonnet, Emmanuel; Freyschlag, Christian F; Pinggera, Daniel; Forster, Marie-Therese; Voss, Martin; Steinbach, Joachim; Loughrey, Carmel; Goodden, John; Banna, Giuseppe; Di Blasi, Concetta; Foroglou, Nicolas; et al.
Abstract: Background: Diffuse low-grade gliomas (DLGGs) are rare and incurable tumors. Whereas maximal safe, functional-based surgical resection is the first-line treatment, the timing and choice of further treatments (chemotherapy, radiation therapy, or combined treatments) remain controversial. Methods: An online survey on the management of DLGG patients was sent to 28 expert centers from the European Low-Grade Glioma Network (ELGGN) in May 2015. It contained 40 specific questions addressing the modalities of use of chemotherapy in these patients. Results: The survey demonstrated a significant heterogeneity in practice regarding the initial management of DLGG patients and the use of chemotherapy. Interestingly, radiation therapy combined with the procarbazine, CCNU (lomustine), and vincristine regimen has not imposed itself as the gold-standard treatment after surgery, despite the results of the Radiation Therapy Oncology Group 9802 study. Temozolomide is largely used as first-line treatment after surgical resection for high-risk DLGG patients, or at progression. Conclusions: The heterogeneity in the management of patients with DLGG demonstrates that many questions regarding the postoperative strategy and the use of chemotherapy remain unanswered. Our survey reveals a high recruitment potential within the ELGGN for retrospective or prospective studies to generate new data regarding these issues.